2006
DOI: 10.1001/archopht.124.10.1451
|View full text |Cite
|
Sign up to set email alerts
|

Altered Tear Composition in Smokers and Patients With Graves Ophthalmopathy

Abstract: To analyze, compare, and contrast tear composition in healthy nonsmokers, smokers who were otherwise healthy, and patients with Graves disease (GD) accompanied by Graves ophthalmopathy (GO) of varying severity. Methods: Reflex tears were collected using Schirmer strips from 37 healthy nonsmokers, 33 otherwise healthy smokers, 51 patients with GD, and 85 patients with GO. Thyrotropin receptor-stimulating activity and serum thyroidstimulating antibodies were measured. Pooled tear samples from healthy nonsmokers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 28 publications
5
21
0
Order By: Relevance
“…30 The exact function of ZAG in tears and its possible role in lipid degradation have only been postulated and not completely clarified. 31,32 In our study, we detected ZAG in both patients and controls, with no statistically significant differences in the respective expression. Our data, do not suggest any significant role of ZAG in the tear stability mechanism, at least as far as mild dry eye is concerned.…”
supporting
confidence: 44%
“…30 The exact function of ZAG in tears and its possible role in lipid degradation have only been postulated and not completely clarified. 31,32 In our study, we detected ZAG in both patients and controls, with no statistically significant differences in the respective expression. Our data, do not suggest any significant role of ZAG in the tear stability mechanism, at least as far as mild dry eye is concerned.…”
supporting
confidence: 44%
“…The altered abundance of this protein in tears was found in several pathological eye conditions. For example, increased abundance of ZAG was found in the tears of keratoconus patients [15], in patients with Grave's ophthalmopathy [41] or keratitis [42]. On the other hand, no significant changes of this protein were noticed in tears from patients with dry eye syndrome [43].…”
Section: Zinc-α2-glycoproteinmentioning
confidence: 99%
“…Many studies have found evidence that the lacrimal gland and tear fluid may be directly involved in the ocular surface damage in TAO [6][7][8][9][10][11][12][13][14]. Eckstein [6] found that ocular surface damage in TAO correlates with reduced tear production, and acinar cells from lacrimal glands were positive for thyotropin receptor (TSH-R), which is considered a target of autoimmunity shared by both thyroid and extrathyroidal sites in TAO.…”
Section: Introductionmentioning
confidence: 99%